O professor coordenador: da legislação à ação - Lasakoswitsck, Ronaldo (2014)
In recent years, the increase of research on teaching coordination reveals, to some consensus, the importance of role of the Teacher Coordinator in public schools, as well as it arouses the need to understand their roles and practices in everyday action, and yet, substantiate the principles for their actions. The concern of the current researchers on Teacher Coordinator falls on themes that articulate the educational and pedagogical processes, the transformation of pedagogical conditions of teaching and teacher s education. Inserted in a scenario marked by the presence of diversity such as teachers, students, community and other professionals, it becomes a priority to define what the actual duties of the position are, and which tasks and professional priorities should play on the school day basis, so there is effectiveness in each performance. This study focus on Teacher Coordinator in public education having as object the Brazilian educational systems, more specifically, the elementary and high schools in the area of Mauá city in the state of São Paulo. The methodological design was defined as descriptive, with the adoption of qualitative methods for collecting and analyzing data. For this purpose, using a literature review, the research was conducted by the enrollment of laws that define and guide the function and performance of the teacher coordinator. Then, documentary analysis, a non-participant observation and in-depth interview study were conducted with the research participants. Social research individuals were intentionally chosen, forming a group of eleven Teachers Coordinators. They answered a structured questionnaire with dichotomous questions regarding their knowledge about the legislation that guides the assignments for the performance and execution of their actions at school. At a later time, during a five-day-working-week, respondents filled out an agenda, revealing what are the main tasks they perform each hour during their week working hours. Using the triangle technique and the content analysis technique (Bardin, 1971), it can be observed that there are differences between the definitions supported by Legislation for the Teacher Coordinator s duties performance and the actions revealed day by day.